The Sopranos. Season six, Part II [videorecording (DVD)] - Weiner, Matthew; Gandolfini, James; Bracco, Lorraine, 1955-; Falco, Edie; Imperioli, Michael, 1966-; Chianese, Dominic, 1931-; Van Zandt, Steve (HBO Video, 2007)
Tony faces a myriad of immediate, stress-inducing crises at home, at work and from the law. Tony's wife Carmela plans for a future she's not sure will arrive, and son AJ and daughter Meadow find that adulthood holds its own surprises.